2022
DOI: 10.1186/s40793-022-00425-1
|View full text |Cite
|
Sign up to set email alerts
|

Metadata harmonization–Standards are the key for a better usage of omics data for integrative microbiome analysis

Abstract: Background Tremendous amounts of data generated from microbiome research studies during the last decades require not only standards for sampling and preparation of omics data but also clear concepts of how the metadata is prepared to ensure re-use for integrative and interdisciplinary microbiome analysis. Results In this Commentary, we present our views on the key issues related to the current system for metadata submission in omics research, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…It is therefore important to follow international guidelines and principles to make data findable, accessible, interoperable and reusable. 90,91 Accordingly, the design of bioinformatics analysis protocols should also include precise planning of data sharing and documentation.…”
Section: Bioinformatics Considerationsmentioning
confidence: 99%
“…It is therefore important to follow international guidelines and principles to make data findable, accessible, interoperable and reusable. 90,91 Accordingly, the design of bioinformatics analysis protocols should also include precise planning of data sharing and documentation.…”
Section: Bioinformatics Considerationsmentioning
confidence: 99%
“…Existing integrative studies linked environmental DNA (eDNA) with functional indicators and showed an overall positive relationship between soil multidiversity and multifunctionality (Delgado‐Baquerizo et al, 2020b), and how trophic regulation shapes soil functioning (Martinez‐Almoyna et al, 2022), while others emphasized the importance of rare taxa for specific processes (Bahram et al, 2022). Recently, new suggestions for unified data infrastructure and metadata entries, which would strongly improve retrieving and reusing data and biobanking, were published by the European Microbiome Support Consortium (Cernava et al, 2022; Ryan et al, 2021). There are a number of prominent research frontiers in this context: Linking existing data and producing new standardized data : We need better practices in data management.…”
Section: Frontiers In Soil Ecologymentioning
confidence: 99%
“…Recently, new suggestions for unified data infrastructure and metadata entries, which would strongly improve retrieving and reusing data and biobanking, were published by the European Microbiome Support Consortium (Cernava et al, 2022;Ryan et al, 2021). There are a number of prominent research frontiers in this context:…”
Section: Frontiers In Data Integrationmentioning
confidence: 99%
“…Nevertheless, there is a striking incongruence between the impressive amount of data produced and the outcome in terms of products from microbiome research both in environmental sciences as well as in the medical field is still limited. In January 2022, only 8000 microbiome-related patents were registered worldwide (Cernava et al 2022, Espacenet – patent search). This incongruence can be explained by multiple reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several researchers opt to furnish only the bare minimum of requisite data, or employ inaccurate terminology when describing their experimental data.These aspects hinder the aggregation of findings through integrative analyses. What we know is that standards are the key to a better usage of omics data for integrative microbiome analysis (Cernava et al 2022) and, at the same time, users require a system that should be easy to use, clearly structured in a hierarchical way, and should be compatible with existing data repositories. Regarding nucleotide sequence data storage, three are the main databases: the Sequence Read Archive (SRA) maintained by the National Center for Biotechnology Information (NCBI) (Kodama et al 2012), the European Nucleotide Archive (ENA) operated by the European Bioinformatics Institute (EBI) (Leinonen et al 2011), and the Sequence Read Archive (DRA) administered by the DNA Data Bank of Japan (DDBJ) (Mashima et al 2017).…”
mentioning
confidence: 99%